2303. Differential Effects on MRSA and MSSA Epidemiology in a Neonatal Intensive Care Unit (NICU) During a Year-Long Surveillance and Decolonization Effort. (26th November 2018) - Zachariah, Philip; Messina, Maria; Hill-Ricciuti, Alexandra; Green, Daniel; Whittier, Susan; Sahni, Rakesh; Saiman, Lisa
Abstract: Background: Staphylococcus aureus (SA) causes morbidity and mortality in the NICU. While surveillance, with decolonization, is recommended for MRSA outbreak control, the impact of such strategies on endemic MSSA infections is less known. We compare the impact of a year-long surveillance and decolonization effort on MRSA and MSSA colonization dynamics and invasive infection rates in the NICU. Methods: All infants hospitalized in our academically affiliated, regional perinatal NICU (1032 annual admissions) between January and December 2017 were screened twice monthly for SA colonization by culturing the anterior nares and three skin sites. Eligible patients with positive SA cultures underwent decolonization with mupirocin and/or chlorhexidine bathing. The following parameters for MRSA and MSSA were compared using frequencies and Fisher's exact tests: 1) Colonization density (proportion of positive surveillance cultures; 2) rates of effective decolonization (proportion of successful decolonization efforts); 3) rates of invasive infections; and 4) mupirocin resistance. Results: Overall, 25 twice monthly surveillance efforts were undertaken from which 1351/1375 (98%) screening cultures were obtained. Screening identified newly detected MSSA vs. MRSA in 145 vs. 20 infants, respectively. Colonization density decreased more for MRSA (Q1 vs. Q4 decrease of 67%) vs, MSSA (Q1 vs. Q4 decrease of 5%). Decolonization was more effective for MRSA (78%) vs. MSSA (71%). Compared with 2016, rates of invasive infections decreased more for MRSA (2.4 vs. 1.6 /10, 000 patient-days, 33%) than MSSA (9.4 vs. 7.8 /10, 000 patient-days, 17%). Prevalence of mupirocin resistance through study period was higher for MSSA (24% vs. 10%). No outbreaks were detected. Conclusion: A year- long surveillance and decolonization effort was more successful in decreasing MRSA colonization density and invasive infections compared with MSSA. These results are likely due to continual importation of MSSA into the NICU from the community. Since MSSA caused more invasive infections than MRSA, strategies primarily aimed to decrease the burden of MRSA need to be modified to decrease the burden of MSSA in NICUs. Disclosures: All authors: No reported disclosures.